Evaluation of the anti-inflammatory effect of an anti-platelet agent crinumin on carrageenan-induced paw oedema and granuloma tissue formation in rats - Rai U.; Rawal A.; Singh S. (My University, 2025)
The present study was designed to explore the anti-inflammatory activity of an anti-platelet agent crinumin, by various in vitro and in vivo inflammation models. Firstly, crinumin protein was purified through cation exchange chromatography; then, in vitro activity was estimated by albumin denaturation assay and HRBC membrane stabilization assay. Carrageenan-induced paw oedema and cotton pellet-induced granuloma models were used for in vivo anti-inflammatory activity assessment in rats. In both models, rats were pre-treated for 7 days with crinumin (25–50 µg/ml) and diclofenac sodium (50 µg/ml). Expression of P-selectin (in serum and plasma) through ELISA and NF-κB (in paw and granulomatous tissues) through western blotting was checked. Our results showed that crinumin at both doses (25 or 50 µg/kg of b.w.) significantly (p < 0.05) reduced the paw oedema formation in a dose-dependent manner in the second phase of inflammation and significant (p < 0.05) reduction of wet and dry weight of granuloma was observed indicating the anti-inflammatory potential of crinumin. Crinumin decreased the expression of P-selectin and NF-κB indicating its potential role in decreasing platelet activation and healing inflammation. Histopathological studies additionally proved the efficacy of drug in treating inflammation. The results of the study suggest that the crinumin might have an inhibitory role in atherosclerosis as platelet aggregation and inflammation are the key processes involved in atherosclerotic disorders. © 2017, Springer International Publishing AG.